2011
DOI: 10.1037/a0022329
|View full text |Cite
|
Sign up to set email alerts
|

How people interpret conditionals: Shifts toward the conditional event.

Abstract: We investigated how people interpret conditionals and how stable their interpretation is over a long series of trials. Participants were shown the colored patterns on each side of a 6-sided die and were asked how sure they were that a conditional holds of the side landing upward when the die is randomly thrown. Participants were presented with 71 trials consisting of all combinations of binary dimensions of shape (e.g., circles and squares) and color (e.g., blue and red) painted onto the sides of each die. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 73 publications
9
105
2
Order By: Relevance
“…It should be noted that an alternative explanation of this developmental trend has been recently proposed by Fugard et al (2011) who suggest an inhibitory account. The trend from a conjunctive to a defective biconditional and then a defective conditional response would reflect a narrowing of the hypothetical scope.…”
Section: A Late Developmental Achievementmentioning
confidence: 92%
See 2 more Smart Citations
“…It should be noted that an alternative explanation of this developmental trend has been recently proposed by Fugard et al (2011) who suggest an inhibitory account. The trend from a conjunctive to a defective biconditional and then a defective conditional response would reflect a narrowing of the hypothetical scope.…”
Section: A Late Developmental Achievementmentioning
confidence: 92%
“…Empirical evidence supporting this proposal is based on a probabilistic truth table task (hereafter, the probability task) in which participants are asked to assess the probability of an If p then q conditional from the probabilities of the four truth-table possibilities p & q, p & not-q, not-p & q, not-p & not-q. Several studies observed that a majority of adults judge the probability of the conditional as the conditional probability P(q|p), that is the probability of p & q divided by the summed probabilities of p & q and p & not-q (Evans, Handley, & Over, 2003;Fugard, Pfeifer, Mayerfofer, & Kleiter, 2011;Oberauer & Wilhelm, 2003;Over, Hadjichristidis, Evans, Handley, & Sloman, 2007).…”
Section: The New Paradigm and The Question Of Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has explored how people can be trying to solve different tasks, for instance, because they interpret the task in different ways (Adler 1984;Politzer 1986;van Lambalgen 2004, 2005;Stenning and Cox 2006;Fugard, Pfeifer, Mayerhofer, and Kleiter 2011). Consider, for example, the premises, 'if the wireless router is switched on, then I can connect to the Internet' and 'the wireless router is switched on'.…”
Section: Introductionmentioning
confidence: 99%
“…One group based their belief on P(q|p), while the other, slightly smaller group based their belief on P(pq) (see also Oberauer & Wilhelm, 2003;Politzer, Over, & Baratgin, 2010, for similar findings). It has since been shown that adults who initially judge a conditional as P(pq) tend to switch to a P(q|p) interpretation as more and more trials are presented (Fugard, Pfeifer, Mayerhofer, & Kleiter, 2011). The influence of P(pq) has been attributed to a form of shallow processing (Evans et al, 2003) and also to individual differences in cognitive ability (Evans, Neilens, & Over, 2008); however, this effect has not been consistently replicated in the literature (Evans, Handley, Neilens, & Over, 2007).…”
mentioning
confidence: 99%